Debt–Equity Conflicts and Efficiency of Distressed Firms: Evidence from Japanese Banker-Directors - Asai, Kentaro; Choi, Dong Beom (Journal of Financial and Quantitative Analysis, 2026)
Abstract This study provides direct evidence of the association between debt–equity conflict and investment efficiency in financially distressed firms. Leveraging a unique institutional setting in Japan, we examine the impact of lender-affiliated directors on the managerial decisions of their borrowers. Although banker-directors do not influence firms at low risks of default, their presence leads to more conservative financial decisions in distressed firms, thereby mitigating shareholder exploitation. They also reduce information frictions to prevent overinvestment and underinvestment. However, despite within-firm efficiency gains, potential spillover effects on other stakeholders raise questions about the broader welfare implications of this debt–equity conflict mitigation.